Molecular dynamics simulation dataset of a kinesin on tubulin heterodimers in electric field - Průša, Jiří; Cifra, Michal (Data in brief, 2024)
We present trajectories from non-equilibrium (in electric field) molecular dynamics (MD) simulations of a kinesin motor domain on tubulin heterodimers with two tubulin heterodimers forming neighbouring microtubule protofilaments. The trajectories are for no field (long equilibrium simulation), for four different electric field orientations (X, -X, Y, -Y) and for the X electric field at four different field strengths. We also provide a trajectory for larger simulation box. Our data enable to analyze the electric field effects on kinesin, which ultimately leads to kinesin detachment. This data set was used to understand the effect of electric field orientation and field strength on the kinetics and energetics of the electro-detachment of kinesin [1].
Keywords: Kinesin; Molecular dynamics; Electric field; Proteins; Microtubule